Production Model Based on Total Productive Maintenance and Systematic Layout Planning to Increase Productivity in the Metalworking Industry - Seminario Mestanza, Carlos Alexander (2023)
The metalworking industry represents one of the most critical factors for the economic development of each country. However, one of its significant bottlenecks is prioritizing some orders over others and the late Maintenance of machinery, which generates stoppages in production lines and delays in processes, which translates into decreased plant productivity. Therefore, to solve these problems, this article proposes a production model based on Total Productive Maintenance and Systematic Layout Planning, which focuses on machinery and human resources to increase the Productivity of companies in this sector. The model simulation was carried out using the Arena software, where a 7.69% improvement in Productivity was obtained and a reduction of up to 32 days in the cycle time. This improvement proposal allows companies in the sector to be more competitive and provides the necessary tools to optimize their processes.